Aplikasi Teknologi Media Tanam Kompos Organik dalam Upaya Peningkatan Kualitas Bibit Pisang Cavendish - Zulzain Ilahude; Fauzan Zakaria; Hayatiningsih Gubali; Mohamad Lihawa (Jurnal Abdimas Terapan, 2026)
Quality Cavendish banana seedlings are needed to support successful cultivation and improve the productivity of banana farming. However, the Women Farmers Group Tunas Hijau in Haya-haya Village, West Limboto District, Gorontalo Regency, still faces several problems in seedling preparation. The growing medium used by the group still depends on ordinary soil, has low organic matter content, poor drainage, and does not yet produce uniform seedling growth. In addition, the technical knowledge of group members in preparing and applying organic compost as a growing medium is still limited. This community service activity aimed to apply organic compost-based growing media technology to improve the quality of Cavendish banana seedlings. The method consisted of program socialization, initial observation of seedling conditions, training on organic compost use, training on growing media formulation, demonstration of growing media preparation with a 2:1:1 ratio of soil, mature organic compost, and rice husk, mentoring during seedling application, and evaluation of seedling growth. The activity involved 20 participants and was carried out collaboratively with students and farmer group members. The results showed increased participant understanding and skills in recognizing mature compost, formulating growing media, filling polybags, transplanting seedlings, and maintaining seedling moisture. This activity provides a simple, low-cost, and applicable technology that can support healthier, more uniform, and sustainable Cavendish banana seedling production.